Wisdom Tooth Extraction On The Lower Jaw Of Patients With Disabilities - Akhrorov Alisher Shavkatovich (Genius Publishing Group, 2024)
This article discusses the complexities and considerations involved in performing wisdom tooth extractions on the lower jaw of patients with disabilities. The process requires special attention due to physical, cognitive, and emotional challenges that may arise, both during and after the procedure. The aim of this study is to highlight the most effective approaches, methods, and technologies for facilitating the extraction process while minimizing risks and ensuring patient comfort.
Keywords: Wisdom tooth extraction; lower jaw; patients with disabilities